COMPARISON OF ALVARADO AND RIPASA SCORE IN DIAGNOSING ACUTE APPENDICITIS TAKING HISTOPATHOLOGY AS THE GOLD STANDARD (The Research of Medical Science Review, 2025)
Background: Acute appendicitis (AA) is a common presentation to the Emergency Department (ED). The diagnosis of AA has traditionally been clinical. As clinical assessment is subjective, there is a wide variation in admission rate, the extent of investigations, negative appendectomies, and delayed diagnosis with subsequent complications. To objectify this clinical diagnosis of AA, several clinical scoring systems have been introduced, of which RIPASA and ALVARADO have been most used in recent years. This study aims to compare the diagnostic accuracy of these two scoring systems in patients presenting to the ED with clinical features suggestive of AA who underwent appendectomy. Objective: To compare the diagnostic accuracy of the ALVARADO and RIPASA scoring systems in identifying acute appendicitis, using histopathology as the gold standard. Materials & Methods: A comparative prospective study was conducted from April to October 2023 in the ED of Combined Military Hospital, Rawalpindi. We applied the ALVARADO and RIPASA scores to 78 patients, aged over 15 years, who presented to the ED with atraumatic right iliac fossa pain, clinical suspicion of AA, and underwent appendectomy. The researcher scoring the patients, the surgeon deciding to operate, and the histopathologist were all blinded to each other's assessments. A RIPASA score ≥7.5 while an ALVARADO score of ≥7 considered positive for acute appendicitis. Histological diagnosis of AA was used as the reference standard and was correlated with the two scoring systems. Sensitivity, specificity and diagnostic accuracy were calculated using standard formula. RESULTS: Of the 78 patients in the study, 59% (n=46) were male and 41% (n=32) were female. Histopathology showed that 65 patients (83.3%) had an inflamed appendix. In contrast, 69 patients (88.5%) had a high RIPASA score, and 67 patients (85.9%) had a high ALVARADO score. The sensitivity of the ALVARADO score was 98.5% with a specificity of 61.5%. On the other hand, diagnostic metrics for the ALVARADO score showed a sensitivity of 95.4% and specificity of 61.5%. Overall diagnostic accuracies for RIPASA and ALVARADO scores were found as 92.3% and 89.74% respectively. CONCLUSION: The findings of our study suggest that both scoring systems are effective diagnostic tools, with the RIPASA score showing a marginally higher diagnostic accuracy. These findings are consistent with current evidence.